Pengaruh Pendidikan Karakter terhadap Konsep Diri Peserta Didik - Riko Riko; Fibria Anggraini Puji Lestari; Iis Dewi Lestari (Universitas Indraprasta PGRI Jakarta, 2019)
The purpose of this study was to determine whether there is an influence of character education on students' self-concepts at SMK Ganesa Satria 2 Depok. The method used in this study is to use correlational surveys with sampling techniques using simple random sampling. While the sample of this study were 100 students at SMK Ganesa Satria 2 Depok. Hypothesis testing analysis using linear regression test, with the results of the hypothesis test there is the influence of character education on the formation of students' self-concept. From the results of the study have an impact on an increase in character education when the tacher give the lesson in class as an effort to form positive self concept of students.